Myoclonic Jerks in an Ex-Preterm Undergoing Hernia Surgery Under Combined Spinal Caudal Block: Is It Time to Revisit the Test Dose? - Lakshmi Kumar; Neethu Padmanabhan; Dimple Elina Thomas; Pramod R. Pillai (Amrita Journal of Medicine)
Myoclonic jerks, while often benign, can indicate underlying issues such as inadvertent intrathecal or intravascular injection of the local anesthetic. In preterm infants, whose physiological responses are often more unpredictable and sensitive, the risk of complications from regional anesthesia may be heightened. We present the management of a possible local anesthetic systemic toxicity in an ex-preterm infant scheduled for an elective left inguinal herniotomy.